Preparation of Wastelage with Poultry Droppings and Oat Forage (Avena sativa) as a Feed for Cattle (Journal of Environmental Science and Natural Resources, 2015)
In this experiment, wastelage was prepared by ensiling Oat forage (Avena sativa) with fresh caged layer excreta (CLE) at varying proportions to investigate the feeding values of wastelage for cattle and protect environment from poultry droppings. Oat forage was mixed with 0, 20, 40 and 60% CLE and 5% molasses in each treatment on dry matter (DM) basis and ensiled in air tight plastic container under room temperature. After 56 days, ensiled mixtures were opened. All the wastelages had desirable aroma, yellowish green color, soft texture and were mould free. The pH, DM, crude protein (CP), crude fiber (CF), ether extra ct (EE), ash, nitrogen free extract (NFE), in vitro organic matter digestibility and metabolizable energy were significantly influenced by levels of CLE. The percentages of DM, CP and Ash (37.34, 18.95 and 14.45, respectively) were highest in wastelage with 60% CLE (p